2023
DOI: 10.1161/circresaha.122.321591
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of Septin4 by SIRT2 (Silent Mating Type Information Regulation 2 Homolog-2) Mitigates Damaging of Hypertensive Nephropathy

Abstract: Background: Hypertension can lead to podocyte damage and subsequent apoptosis, eventually resulting in glomerulosclerosis. Although alleviating podocyte apoptosis has clinical significance for the treatment of hypertensive nephropathy, an effective therapeutic target has not yet been identified. The function of septin4, a proapoptotic protein and an important marker of organ damage, is regulated by post-translational modification. However, the exact role of septin4 in regulating podocyte apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Recent studies have shown that septin4 promotes hypertensive kidney injury by activating the acetylation of K174 (K174Q). Septin4–K174R is one of the renoprotective factors that ameliorates Ang II-induced hypertensive kidney injury ( 47 ). In addition, an increase in blood pressure leads to arterial stiffness, which eventually affects the arteries and causes glomerular lesions ( 48 ).…”
Section: Relationship Between Hypertension and Kidney Diseasementioning
confidence: 99%
“…Recent studies have shown that septin4 promotes hypertensive kidney injury by activating the acetylation of K174 (K174Q). Septin4–K174R is one of the renoprotective factors that ameliorates Ang II-induced hypertensive kidney injury ( 47 ). In addition, an increase in blood pressure leads to arterial stiffness, which eventually affects the arteries and causes glomerular lesions ( 48 ).…”
Section: Relationship Between Hypertension and Kidney Diseasementioning
confidence: 99%
“…8 Meanwhile, the specific role of SIRT2 in kidney disease remains unclear. In the article by Zhang et al, 4 authors proposed that SIRT2-mediated deacetylation of Septin4-K174 attenuates hypertensive renal injury. Indeed, they showed that Sirt2 depletion in mice and SIRT2-knockdown in renal podocytes, Septin4-K174 remains hyperacetylated, and this exacerbates hypertensive renal injury.…”
Section: Dikalov and Kirabomentioning
confidence: 99%
“…7 Septin4 expression is regulated by the Notch pathway and ubiquitination at K174 promote degradation of Septin4 through the ubiquitin-proteasome system. 6 In this article, 4 authors proposed that posttranslational modification of Septin4 by acetylation at K174 promotes hypertensive renal injury. Indeed, they found that Septin4-K174Q acetylation mimetic mutation in mice exacerbates angiotensin II-induced hypertensive renal injury and superoxide scavenger TEMPOL (4-Hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl) protects from oxidative stress and significantly reduces the damaging effects in Septin4-K174Q mice.…”
Section: Article See P 601mentioning
confidence: 99%
See 2 more Smart Citations